Sayyid Qutb: the life and legacy of a radical Islamic intellectual - Toth, James (Oxford University Press, 2013)
James Toth traces the life and thought of Sayyid Qutb, the Egyptian thinker and Islamist martyr branded by The New York Times Magazine as "The Philosopher of Islamic Terror." By returning to Qutb's writings, Toth draws a complex portrait of Qutb, one that moves beyond the cartoonish descriptions of him as the evil genius lurking behind today's terrorists